CROSS-LINGUISTIC ASYMMETRIES AND TRANSLATION UNIVERSALS IN SLAVIC-GERMANIC LANGUAGE CONTACT - Rakhmatilloeva , Rukhshonabonu (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This study examines cross-linguistic asymmetries and translation universals in contact situations between Slavic and Germanic languages, with particular focus on structural convergence patterns and directional asymmetries in translation processes. Through corpus analysis of parallel texts and contact phenomena in border regions, we identify systematic patterns of linguistic influence that reveal both universal tendencies and language-specific constraints. Our findings demonstrate that translation universals manifest differently depending on the typological distance between source and target languages, with Slavic-Germanic pairs showing distinct asymmetrical patterns in morphological complexity reduction, syntactic calquing, and lexical borrowing strategies. The research contributes to understanding how genetic linguistic distance interacts with translation universals to produce predictable contact outcomes.